Global trends of academic mobility in the context of qualified migration. The case of the Universidad Nacional del Sur, Bahía Blanca city, Argentina (Huellas, 2021)
Academic mobility is a process that has acquired increasing visibility in recent decades, favored by the articulation of global logics, links and networks that operate at various scales. The dissemination of academic offers offered by various programs and agreements, agreed between Higher Education Institutions, has been one of the main factors that explain this type of mobility, framed within skilled migration. The configuration of mobility spaces depends on institutional agreements, scholarships, quality standards, institutional prestige and competitiveness in the scientific domain. The objective of this study is to analyze the current trends in skilled migration in the context of the Internationalization of Higher Education, taking as a case study the Universidad Nacional del Sur (UNS) for the period 2007-2019. A mixed quali-quantitative methodology was adopted through semi-structured interviews and the processing of official data available at the UNS Internationalization Undersecretary. Although academic mobility in Argentina is a representative phenomenon within Latin American migratory movements, this dynamism is still not very significant in comparison with other regions, such as the European Union, where academic exchanges are more consolidated.
Keywords: skilled migration; internationalization of higher education; academic mobility; Universidad Nacional del Sur